ECONOMIC VIEWS OF P.J. PRUDHOMME (Economic journal of Lesya Ukrainka Volyn National University, 2025)
Introduction. The article examines Proudhon's thoughts and ideas on society's economic progress. He considered the driving force of its development to be the individual freedom of independent small producers built on small private property and free and fair disposal of manufactured products.The purpose of the article. The article's purpose is to complete a comprehensive study of the foundations and economic views of P.J. Proudhon.Methods. To write an article on the economic ideas of P.J. Proudhon, several methodological approaches were used, including the historical and biographical approach allowed us to consider the formation of his views in the context of the era and his life; the thematic approach involves structuring the article around Proudhon's key ideas, such as individual freedom, small property, the theory of value, mutualism, interest-free lending and criticism of the state organisation; the comparative and analytical approach allowed us to compare his ideas with other economic theories and evaluate them.Results. The article examines the scientist's development of the theory of 'constituted value', the justification of the concept of 'mutualism' (principles of mutual benefit, equality, and justice), and elucidation of the idea of intereste results of one's labor to be an obstacle to receiving non-labor income.Conclusions. P.J. Proudhon opposed social and state organisations. He argued that society can exist without a governmental system.
Keywords: economic views, economic progress, individual freedom, small producers, small private property, free disposal of products, constituted value, mutualism, mutual benefit, equality, justice, interest-free lending, non-labor income, public-state organisation, self-government of society.